Evaluation of sunobinop for next-day residual effects in healthy participants - Cipriano, Alessandra; Kapil, Ram P.; Zhou, Mingyan; Shet, Manjunath S.; Harris, Stephen C.; Apseloff, Glen; Whiteside, Garth T. (Frontiers in Pharmacology, 2024)
Sunobinop is a novel, potent, selective partial agonist at nociceptin/orphanin FQ peptide (NOP) receptors. The primary objective of this randomized, double-blind, placebo-controlled study was to assess the next-day residual effects of an evening dose of sunobinop in healthy participants. Participants were randomized into 1 of 5 treatment sequences. Treatment consisted of 1 dose each of sunobinop 0.2, 0.6, 2, and 6 mg suspension and placebo suspension. Key pharmacodynamic (PD) measures included the digit symbol substitute test (DSST), Karolinska sleepiness scale (KSS), and body sway. The randomized safety population consisted of 25 participants.The DSST, KSS, and body sway showed dose-dependent effects following the administration of sunobinop, with no significant differences versus placebo at sunobinop doses <2 mg. At sunobinop 2 mg, PD effects were relatively small in magnitude and inconsistent. The last timepoint where significant differences between sunobinop 2 mg and placebo on the DSST, KSS, and body sway were observed was at 12 hours, 16.5 hours, and 13.5 hours postdose, respectively. Sunobinop 6 mg resulted in larger and consistent PD effects, with significant differences from placebo at all timepoints up to 16.5 to 18 hours postdose. Somnolence was the most frequently reported adverse event (AE), and all AEs were mild-to-moderate. No deaths occurred during the study or discontinuations due to an AE. Overall, a nighttime oral dose of sunobinop up to 2 mg was safe and generally well tolerated in healthy participants with limited next-day residual effects that were consistent with other sedative/hypnotic drugs.